THE DEVELOPMENT OF DIGITAL MONEY IN JAPAN: A STUDY OF LITERATURE - Silvia Sadiah (Institute of Computer Science (IOCS), 2022)
The rise of cash, which has become less visible in transactions of commodities, services, and investments, is one of the hallmarks of modern economic society. Over a lengthy period of time, a cashless society has emerged, centered on wholesale distribution. Non-cash payments in retail distribution, in particular, have increased and accelerated in recent years, as has the use of non-cash payment methods such as credit cards, prepaid cards, and electronic money. Cashless payments have gotten a lot of attention since the new coronavirus epidemic broke out in early 2020, with the goal of expanding online payments. The hygiene element, because electronic money is not touched even in businesses that take credit card payments and so on, is one of the factors that is driving up non-cash payments. This limits contact chances between personnel and customers. The usage of non-cash payments is also encouraged by the new lifestyle and industry guidelines. The findings of this study reveal the impact of non-cash payment development on Japanese society.